LAND USE CHANGE ASSESMENT AND ITS PROJECTION IN BATANGHARI RIVER BASIN, SUMATERA, INDONESIA - Utami, Nurya; Sapei, Asep; ., Apip (Research Center for Limnology, 2017)
The study followed about changes in land use in the region of Batanghari river basin. Land cover maps derived from supervised classification of satellite imagery LANDSAT MS / ETM / OLI. The images in the study area were categorized into six classess, namely water body, settlement, agriculture, bush, openland and forest. The validation for classification result was using Kappa Statitistic with average yield of 85% -95%. Based on the classification results, the biggest extent of land cover change is forest areas into agricultural areas. Changes in the area of certain types of land cover can be seen in the change detection matrix. Data extents of land use was used to calculate the land use demands from recent past to near future. Two scenarios were used to produce land use projection from 2016 to 2045. First projection, generating a dominant land use type of agriculture. Addition of the areas about 22% from 2015, which is around 3.148.100 ha. While forest area decrease almost 50%. Second scenario is fast growth scenario, producing a forest areas about 450.275 ha. Whereas agriculture area reaches a maximum changes of 3.300.742 ha.